Φαινολογικά στάδια των ποιοτικών χαρακτηριστικών τεσσάρων οινοποιήσιμων ποικιλιών αμπέλου - Αντωνίου, Μιχάλης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The importance of viticultureis widely known for its many uses, but mainly because of winemaking, which is one of the most profitable industries of the world. The purpose of this work was to record the phenological stages and to determine the quality characteristics of the four wine grape varieties 'Syrah', 'Merlot', 'Mataro' and 'Xynisteri'. The grapes of the four varieties were harvested from the village of Pachna in the province of Limassol. The 'Syrah' variety was harvested on 02/08, 'Merlot' on 03/08, 'Mataro' on 11/08 and 'Xynisteri' on 05/09. Grapes from the four varieties were harvested at the stage of technological maturation in order to determine the qualitative characteristics. In addition, the phenological stages of the grapes, were monitored every fifteen days. The measurements taken during the determination of the qualitative characteristics of the varieties were the weight of the crimp, the weight of the berries, the total weight of the grape, the number of berries of each grape, the weight of thousands of berries, the total soluble solids (TSS), total acidity, pH, the coefficient of maturation and color markers (intensity and hue). Results showed that ‘Xynisteri’ has the greatest grape weight compared to the other varieties. The levels of the TSS in the four varieties differ, since there is a 6% difference between the 'Syrah' variety with the highest TSS content compared to the lowest content of ‘Xynisteri’. The pH in the four varieties as expected was close to 3 and the results on total acidity showed differences among the examined cultivars. Also, regarding the phenological stages we conclude that the earliest variety is ‘Syrah’, while the latest is ‘Xynisteri’. Comparing the results of this work with other studies, we come that the role of 'terroir' is very important in the composition and qualitative attributes of each variety.
Keywords: Viticultureis; Winemaking; Phenological stages; Syrah; Merlot; Mataro; Xynisteri; Grapes; Φαινολογικά στάδια; Οινοποίηση; Syrah; Merlot; Mataro; Ξυνιστέρι; Σταφύλια